6-Gingerol protects intestinal barrier from ischemia/reperfusion-induced damage via inhibition of p38 MAPK to NF-κB signalling. (May 2017) - Li, Yanli; Xu, Bin; Xu, Ming; Chen, Dapeng; Xiong, Yongjian; Lian, Mengqiao; Sun, Yuchao; Tang, Zeyao; Wang, Li; Jiang, Chunling; Lin, Yuan
Graphical abstract: Abstract: Intestinal ischemia reperfusion (I/R) injury caused by severe trauma, intestinal obstruction, and operation is one of the tough challenges in clinic. 6-Gingerol (6G), a main active ingredient of ginger, is found to have anti-microbial, anti-inflammatory, anti-oxidative, and anti-cancer activities. The present study was designed to characterize the potential protective effects of 6G on rat intestinal I/R injury and reveal the correlated mechanisms. Rat intestinal I/R model was established with clamping the superior mesenteric artery (SMA) and 6G was intragastrically administered for three consecutive days before I/R injury. Caco-2 and IEC-6 cells were incubated under hypoxia/reoxygenation (H/R) conditions to simulate I/R injury in vitro . The results showed that 6G significantly alleviated intestinal injury in I/R injured rats by reducing the generation of oxidative stress and inhibiting p38 MAPK signaling pathway. 6G significantly reduced MDA level and increased the levels of SOD, GSH, and GSH-Px in I/R injured intestinal tissues. 6G significantly decreased the production of proinflammatory cytokines including TNF-α, IL-1β, and IL-6, and inhibited the expression of inflammatory mediators iNOS/NO in I/R injured intestinal tissues. The impaired intestinal barrier function was restored by using 6G in I/R injured rats and in both Caco-2 and IEC-6 cells characterized by inhibiting p38 MAPK phosphorylation, nuclear translocation of NF-κB, and expression of myosin light chain kinase (MLCK) protein. 6G also reduced the generation of reactive oxygen species (ROS) in both Caco-2 and IEC-6 cells. In vitro transfection of p38 MAPK siRNA mitigated the impact of 6G on NF-κB and MLCK expression, and the results further corroborated the protective effects of 6G on intestinal I/R injury by repressing p38 MAPK signaling. In conclusion, the present study suggests that 6G exerts protective effects against I/R-induced intestinal mucosa injury by inhibiting the formation of ROS and p38 MAPK activation, providing novel insights into the mechanisms of this therapeutic candidate for the treatment of intestinal injury.